THE THE INFLUENCE OF INTERPERSONAL SKILL ON INSTAGRAM SOCIAL MEDIA MARKETING ON ERIGO FASHION PRODUCT PURCHASE DECISIONS - Rifqi Agianto (PROGRAM STUDI ILMU KOMUNIKASI, 2022)
Interpersonal skill is a communication skill that must be possessed by business actors to help launch a business that is being run both in increasing sales, attracting consumer attention and providing excellent service to consumers. The application of interpersonal skills in social media marketing is often done by business people, one of which is Erigo. Erigo is one of the fashion brands in Indonesia which was founded by Muhammad Saddad since 2013 until now and continues to be popular among teenagers to adults. The purpose of this study was to determine how much influence Interpersonal has on consumer purchasing decisions on Erigo products. This study uses a quantitative approach by conducting a survey in the form of filling out a questionnaire by emphasizing the characteristics and criteria of the respondents. The sampling technique was carried out by purposive sampling with a sample of 100 respondents who had the criteria of ever buying Erigo products and following the Erigo Instagram account. The questionnaire data that has been obtained is then processed using the validity test, reliability test, and normality test. The data analysis used is simple linear regression t-test and coefficient of determination test results. The results of this study indicate that there is a fairly large and significant influence of 67.6% between interpersonal skills on social media marketing Istagram with purchasing decisions for Erigo products and the remaining 32 ,4% influenced by other factors.